Ayurvedic Management of Autoimmune Disorders: A Systematic Review - Suparya , Subash P; Giri, P V (International Research Journal of Ayurveda & Yoga, 2022)
In autoimmune disorders, immune cells are mistakenly attacking our own cells and appear as a curse to this society. This study systematically reviewed the published clinical articles in PubMed regarding Ayurvedic management of autoimmune disorders. For that purpose, articles available in PubMed were searched and analyzed for scientific evidence. Out of seventy-three records found, ten related studies were included in the final analysis and showed Ayurvedic therapies had an effect on the management of autoimmune disorders. Even though autoimmune thyroid disease and Type 1 Diabetes are the most common of these conditions, scientific publications are more on rheumatoid arthritis. However, the lack of a strong voice in scientific journals was also well represented. At the same time, the management of autoimmune disorders will also open a new door for developing super-speciality clinics in Ayurveda and will become the need of the present era.